2005
DOI: 10.1103/physrevb.72.035409
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Raman spectroscopy of single-wall carbon nanotubes under pressure

Abstract: International audienceWe performed high pressure resonant Raman experiments on well characterized purified single-wall carbon nanotubes up to 40 GPa using argon as pressure transmitting medium. We used two different excitating wavelengths, at 632.8 nm and 514.5 nm. In contrast with other studies no clear sign of phase transformation is observed up to the highest studied pressure of 40 GPa. Our results suggest that the progressive disappearance of the radial breathing modes observed while increasing pressure sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
103
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 35 publications
9
103
3
Order By: Relevance
“…6) as is expected in case of SWCNT bundles under stress. [32][33][34] This indicates that the SWCNTs forming the network are not under stress post deposition of ta-C.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 96%
See 1 more Smart Citation
“…6) as is expected in case of SWCNT bundles under stress. [32][33][34] This indicates that the SWCNTs forming the network are not under stress post deposition of ta-C.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 96%
“…[32][33][34] The Raman spectra of samples (on silicon substrates) post deposition of 20 nm and 50 nm of ta-C were acquired and are shown in Figs. 6(a) and 6(b), respectively.…”
Section: B Evaporated Carbon Coated Samplesmentioning
confidence: 99%
“…High-pressure results on SWNTs have been summarized by Loa. 40 Fewer high-pressure reports appeared 44 on MWCNTs probably because of their similarity with graphite. The large diversity of reported data for SWCNTs can be attributed to differences in their syntheses.…”
Section: Summary Of Pressure-and Temperature-induced Effects Of the Dmentioning
confidence: 99%
“…We use argon, oxygen, and methanol-ethanol in the proportion 4:1. Recent studies of Merlen et al 8,9 on CNT bundles ͑CNTs grown by the arc discharge method͒ show no frequency dependence on the media. In this study we use CNTs grown using the catalytic chemical vapor deposition method ͑CCVD͒, which leads to the formation of individual CNT and small bundles allowing nanoscale pressure effects to be investigated.…”
mentioning
confidence: 95%
“…This is supported by the fact that in the case of tubes in a bundle ͑i.e., without surrounding pressure medium͒ no medium effect is observed. 8 The medium dependence of the shape of the optical phonon band also indicated that the DWCNTs are surrounded by the pressure transmitting medium. We conclude that the DWCNTs here are surrounded by the pressure medium.…”
mentioning
confidence: 97%